HUBUNGAN ANTARA KARAKTERISTIK MASYARAKAT DENGAN PEMANFAATAN PELAYANAN IMUNISASI PENTAVALEN BOOSTER DALAM PENCEGAHAN DIFTERI DI WILAYAH KERJA PUSKESMAS HALMAHERA KOTA SEMARANG - Antonia Novika Siswati; Ayun Sriatmi; Antono Suryoputro (Jurnal Kesehatan Masyarakat (Undip), 2018)
The Ministry of Health determined Indonesia with diphtheria Extraordinary Event status(KLB) at November 2017.Of the 20 provinces, Central Java entered the top of 11 provinces with diphtheria extraordinary event status. There were 2 cases of diphtheria in Semarang City at 2017.Pentavalent booster immunization is a vaccine to prevent diphteria. From the 4 puskesmas that have diphtheria cases in 2016-2017, Halmahera’s puskesmas has the lowest coverage in achieving pentavalent booster immunization.This research aims to find the relation between community characteristics with the utilization services of pentavalen booster immunization in diphteria prevention at the working area of Halmahera’s puskesmas in Semarang City.This research uses a quantitative method with a cross sectional study approach. The population were all mothers who had children aged 3 - 5 years in July 2018 and the sample were 100 mothers that chosen by random sampling technique namely cluster sampling.Data analysis using univariate and bivariate analysis with Chi-Square test. The results showed that the utilization services of pentavalent booster immunization at the working areaof Halmahera’s puskesmas was still low(31%). The result of bivariate analysis using Chi-Square test shows that the characteristics were not related with the utilization services of pentavalent booster immunization. Suggestions for puskesmas are icreasing the promotion of pentavalent booster immunization by providing counseling and personal selling with health cadres in the region.